''[S.S.] Beothic at anchor at new detachment at Bache Peninsula.'' - Job, John (William John), b. 1944- (1926)
The S.S. Beothic anchored at the Bache Peninsula, North West Territories (now Nunavut) at the Royal Canadian Mounted Police detachment. This collection consists of photographs taken from two Job family albums, reflecting their business ventures, family activities and historical events.